DAMPAK LALULINTAS MENERUS PADA JARINGAN JALAN DI KOTA METRO - Sasana Putra (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2008)
Abstract Metro is one of the cities in Lampung Province, Indonesia. It is located between Eastern Lampung and Central Lampung Districs and becomes a junction of two regional highway, i.e. Central Sumatera Highway and Sumatera Eastern Coast Highway. This position produces high traffic flow on route assignment in Metro City. This study aims to observe the impact of trough on road network performance in Metro City. TRANPLAN is used to model the performance of the network and the result is be compared with the field condition. The results indicate that the potency of daily trough traffic load in Metro City is about 24,99% from the whole interzones movement. The research also indicate that there is no problem with the performance of traffic network in Metro City for time being (with error margin less than 20%). The problem of traffic jamp is predicted happens in 2013 where V/C ratio of several main roads in Metro City are more than 0,8. Trought traffic load contributes about 21% of V/C ratio of traffic network in Metro City. Keywords: trought traffic, OD matrix, route assignment, V/C ratio